Reclaiming a Democratic Political Community (In Factis Pax: Journal of Peace Education and Social Justice, 2009)
A Review of Paul Theobald, Education Now: How Rethinking America’s Past Can Change Its Future (Boulder: Paradigm Publishers, 2009).